Interrogation on Optical Properties of Electrolyte Minerals, TSS and Turbidity in Water - Spectrophotometer and IOP Profiler Based Hyperspectral Analysis Approach - M, Ramaraj; Sivakumar, Ramamoorthy (Trends in Sciences, 2023)
The optical properties of total suspended solids, turbidity, and electrolyte minerals in water such as sodium, potassium, and calcium were studied under laboratory and field-oriented conditions. Spectrophotometer and Wet Lab Instrument Inherent Optical Properties profiler have been used to measure the optical properties. The polynomial fit between the field measured absorption spectra and laboratory measured absorption spectra of each mineral explains in detail the chemical water quality parameters and optical properties. The spectrophotometrically derived absorption coefficient of electrolyte minerals such as sodium (1,000 ppm), potassium (100 ppm), and calcium (1,000 ppm), TSS (500 ppm) and Turbidity (100 NTU) makes virtuous correlation with the IOP profiler measured absorption coefficient donates the best polynomial fit R2 values of 0.9076, 0.9019, 0.9645, 0.9823 and 0.9354 respectively. Results in this study exhibits that, the absorption coefficient of electrolyte minerals, TSS, and Turbidity in water increases with increasing their concentrations at the wavelengths range from 200 to 300 nm. HIGHLIGHTS The absorption coefficient values are increasing with the increasing concentration of sodium as well as for calcium and Total suspended solids The absorption spectra of potassium are exponentially increasing with decreasing wavelength The absorption curves show an evolution from a solitary, well defined absorption trough at 550 nm at lower turbidity values to a broader, more flat-topped absorption encompassing from 550 to 650 nm at higher turbidity levels GRAPHICAL ABSTRACT